The Implication of Digital Organisational Culture on Firm Performance - Pradana, Mahir; Silvianita, Anita; Syarifuddin, Syarifuddin; Renaldi, Renaldi (Frontiers in Psychology, 2022)
Digital technologies have become a major factor for innovation in the business environment. Organizations have taken advantage from digitized data and information to increase performance. However, there are still few research focusing on the effect of digitalization on organizational culture, which in the end will affect performance. We develop this research by exploring a proposed model involving digital organizational culture with the final goal to enhance organizational performance. The research involved 263 managers of state-owned company in Indonesia. We analyzed the theoretical model by using structural equation modelling and process the data using SmartPLS version 3 software. We conclude that digital organizational culture can become an essential factor in improving digital strategy and performance. However, business digitalization does not really affect digital organizational values.